The role of baamboozle in promoting Indonesian students’ English vocabulary achievement - Hakim, Tuffa Hulwati; Syafrizal, Syafrizal; Nurlely, Ledy (Educenter : Jurnal Ilmiah Pendidikan, 2025)
Limited vocabulary among elementary learners hinders effective English communication and calls for more engaging instructional media. This research investigated the influence of the Baamboozle platform on the English vocabulary achievement of fourth-grade students in the 2024/2025 academic year at MI Islamiyah Ciwaru. The study adopted a quasi-experimental design with a nonequivalent control group, consisting of 64 participants divided equally into experimental and control classes. Students’ vocabulary achievement was assessed through pre-test and post-test instruments, and the results were analyzed using descriptive statistics, normality and homogeneity checks, as well as an independent samples t-test via IBM SPSS Statistics 25. Findings indicated that the experimental group’s average score improved from 56.25 to 86.56, whereas the control group’s average rose from 55.94 to 79.37; the between-group difference was statistically significant (p = 0.015). The findings indicated that Baamboozle was an effective and engaging medium for improving elementary students’ English vocabulary mastery